Innovative Smart Parking System for Kluang Mall - Yusuf, Ismail; Arbain, Siti Hajar Binti (Applied Information Technology And Computer Science, 2026)
This creative Smart Parking System project describes how a solution to reduce parking inefficiencies at Kluang Mall was designed, developed, and assessed. The system was created using a web-based architecture with HTML, CSS, and JavaScript for the front-end, PHP, and MySQL for the back end, and most importantly Python with OpenCV for License Plate Recognition (LPR) to address problems like a lack of real-time availability information, restricted payment flexibility, and ineffective manual management. A comprehensive administrative dashboard for monitoring parking data, payments, and facility status is one of the key features, along with automatic vehicle entrance and departure via LPR, real-time parking spot availability, and secure online payment integration with Stripe. The system's resilience, usability, and secure functioning were confirmed by extensive testing, which included User Acceptance Testing, System Testing, and Security Testing. The findings demonstrate that the created system greatly improves user convenience and operational efficiency, providing a scalable, dependable, and forward-thinking answer to modern parking difficulties.